Dynamic exergy and economic assessment of the implementation of seasonal underground thermal energy storage in existing solar district heating. (15th December 2022) - Veyron, Mathilde; Voirand, Antoine; Mion, Nicolas; Maragna, Charles; Mugnier, Daniel; Clausse, Marc
Abstract: In this paper, an exergoeconomic approach is proposed to assess the impact of the integration of a Borehole Thermal Energy Storage (BTES) in the existing district heating of the city of Chateaubriant in France. To do so, a dynamic simulation is run over ten years of operation. The model includes a new approach for cost calculation of short-term thermal storage, which is extended to seasonal BTES. The analysis of the system operation at yearly and daily scales revealed several issues. Hence, without redesigning the existing installation, it was found that a non-comprehensive control strategy results in an increase of fossil fuel share by 1.2%. At the BTES scale, from an exergoeconomic point of view, the charging stage is found particularly sensitive to the dynamic. For example, charging the BTES at low temperature increases of the specific cost of the heat stored. Hence, it is shown that some exergoeconomic indicators, like the specific cost of stored heat, could be relevant for designing and operating heating systems with borehole thermal energy storage. Highlights: Impact of seasonal thermal energy storage on an existing solar district heating is assessed. A dynamic exergo-economic approach is proposed to identify the inefficiencies. Yearly performance decrease because of improper operation between storage and generators. Average and standard deviation values illustrate the wide spread distribution of indicators. Several inefficiencies are identified during seasonal storage charging mode.